The Implementation of Picture Word Inductive Model (PWIM) in Writing Recount Text of The Eleventh Grade Students at SMA NU Gombengsari in The Academic Year 2024/2025 - Elsa Resti Yunita; Farchan Ardiyan; Siprianus Rhaki; Khanin Nabilah; Abdul Halim (MAN Insan Cendekia Jambi, 2025)
This study aims to investigate the effectiveness of implementing the Picture Word Inductive Model (PWIM) in enhancing students’ skills in writing recount texts. Conducted at SMA NU Gombengsari in the academic year 2024/2025, this pre- experimental study applied a one-group pretest-posttest design with 17 students as the respondents. Students were assessed on their ability to write recount texts before and after receiving instruction through PWIM. The data collection method utilized writing tasks scored via a standardized rubric, and data analysis was performed using a paired sample t-test. The results revealed a significant improvement in students' writing scores after the intervention. The mean posttest score (73.82) was higher than the pretest score (58.82), with a t-test value of 7.63 exceeding the t-table value of 1.74 at a 5% significance level. The findings indicate that PWIM positively influences students' abilities in composing recount texts by enriching their vocabulary, improving structure, and enhancing engagement.